2017
DOI: 10.1530/eje-16-0990
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Genetics of human bone formation

Abstract: Throughout life, bone is continuously remodelled to be able to fulfil its multiple functions. The importance of strictly regulating the bone remodelling process, which is defined by the sequential actions of osteoclasts and osteoblasts, is shown by a variety of disorders with abnormalities in bone mass and strength. The best known and most common example of such a disorder is osteoporosis, which is marked by a decreased bone mass and strength that consequently results in an increased fracture risk. As osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 133 publications
0
18
0
4
Order By: Relevance
“…Bone, a dynamic tissue, experiences continuous remodeling of osteoblast formation and osteoclast resorption (Hadjidakis & Androulakis, 2006; B. Zhao, 2017). The imbalance of osteoclastic resorption and osteoblastic bone formation may result in pathological conditions of bone structure, including osteoporosis, osteonecrosis, and Paget's disease (Boudin & Van Hul, 2017). Osteolytic disease occurs when the enhancement of formation and function for osteoclasts, or the relatively impairment of formation and function for osteoblasts (Kular, Tickner, Chim, & Xu, 2012; Xu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone, a dynamic tissue, experiences continuous remodeling of osteoblast formation and osteoclast resorption (Hadjidakis & Androulakis, 2006; B. Zhao, 2017). The imbalance of osteoclastic resorption and osteoblastic bone formation may result in pathological conditions of bone structure, including osteoporosis, osteonecrosis, and Paget's disease (Boudin & Van Hul, 2017). Osteolytic disease occurs when the enhancement of formation and function for osteoclasts, or the relatively impairment of formation and function for osteoblasts (Kular, Tickner, Chim, & Xu, 2012; Xu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…*p < .05 and **p < .01 for statistical significance comparing the treatment group with control groups The excessive osteoclast formation and activity are featured in a wide range of osteolytic diseases (T Nakamura et al, 2007),. including osteoporosis(Boudin & Van Hul, 2017), periodontitis (D. E Lee et al, 2015),. rheumatoid arthritis(Durand et al, 2011; Nose et al, 2009), and the aseptic loosening of orthopedic implants(Jamsen et al, 2017).…”
mentioning
confidence: 99%
“…A recent systematic review and meta-analysis study demonstrated significant correlations between vitamin D receptor (VDR) polymorphisms, such as VDR ApaI and VDR FokI, and susceptibility to postmenopausal osteoporosis 42 . Such studies have offered us the opportunity to understand the bone density issue at the genetic level and increased our knowledge about osteoporosis 43 . A GWAS study integrating co-expression network data found that SPTBN1 (spectrin, beta, non-erythrocytic 1) and MARK3 (MAP/microtubule affinity-regulating kinase 3) were causal genes at BMD GWAS loci 44 .…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of this century, an additional role of WNT signaling was discovered following new gene identifications in some rare monogenic skeletal dysplasias. As explained in detail below, the study of conditions with either decreased or increased bone mass resulted in the identification of mutations in several genes involved in especially canonical WNT signaling (5). The most recent revision of the nosology and classification of genetic skeletal disorders (6) includes 461 different diseases.…”
Section: Introductionmentioning
confidence: 99%